Caring for our infants: parents' antenatal childcare intentions and nine-month reality. Issue 1 (2nd January 2019) - Atatoa Carr, Polly E.; Reese, Elaine; Bird, Amy L.; Bandara, Dinusha K.; Grant, Cameron C.; Morton, Susan M. B.
Abstract: Infants are increasingly cared for by adults other than their parents. Here we describe non-parental infant care within a diverse cohort; and investigate the relationship between parents' antenatal intentions and actual infant care. 6822 New Zealand women were recruited during pregnancy and asked about their intentions for childcare. Non-parental care was assessed when infants were nine months old: 1717 (25%) of the 6853 cohort children were receiving more than 8 h per week of regular non-parental care. In comparison with infants of European mothers, infants of Asian or Pacific mothers were more likely to be cared for by extended family; and infants of Māori mothers were more likely to receive centre-based care. Infants from families with lower household incomes, living in more deprived areas were more likely to be cared for by family. When their infants were nine months old, mothers from low- to medium-income households were less likely to be using the type of non-parental care they had intended antenatally, and the same was true when their children were aged 2 years.